2006
DOI: 10.1002/eat.20266
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study investigating disordered eating during the transition to motherhood among Chinese women in Hong Kong

Abstract: Findings suggested that the transition to motherhood is a period of stress that may either precipitate or exacerbate disordered eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 46 publications
3
36
0
7
Order By: Relevance
“…Most of these studies show that eating symptomatology increases in mothers after childbirth as compared to the prenatal period. 4,5 Though these studies provide valuable information on the devel-opment of eating problems in mothers from the prenatal to postnatal period, they provide, however, limited insight into how having children influences eating problems in a long-term perspective. For example, research has shown that eating behavior in pregnancy and shortly after delivery can substantially differ from eating behavior in other periods of life; 4,5 there is as such a need for longitudinal studies that investigate how eating problems develop from before pregnancy and over a longer period after childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies show that eating symptomatology increases in mothers after childbirth as compared to the prenatal period. 4,5 Though these studies provide valuable information on the devel-opment of eating problems in mothers from the prenatal to postnatal period, they provide, however, limited insight into how having children influences eating problems in a long-term perspective. For example, research has shown that eating behavior in pregnancy and shortly after delivery can substantially differ from eating behavior in other periods of life; 4,5 there is as such a need for longitudinal studies that investigate how eating problems develop from before pregnancy and over a longer period after childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…Assim, sugerem quatro factores preditores de recaída em comportamentos bulímicos: comportamentos bulímicos persistentes durante a gravidez, história de anorexia nervosa antes do diagnóstico de bulimia nervosa, diabetes gestacional e gravidez não planeada. Num outro estudo (Lai, Tang, & Tse, 2006) com uma amostra de indivíduos sem diagnóstico de perturbação do comportamento alimentar, os autores encontraram valores de perturbações alimentares duas vezes superiores nos seis meses pós-parto, sendo os preditores do estudo a falta de suporte do companheiro, fraca ligação mãe-bebé, perturbação alimentar durante a gravidez e depressão pós-parto. Também constataram que os episódios de compulsão alimentar, purgação e cognições de perturbação alimentar melhoram com a gravidez, apesar de tenderem a níveis pré-gravídicos no período pós-parto.…”
Section: Perturbações Do Comportamento Alimentar E Gravidezunclassified
“…Também constataram que os episódios de compulsão alimentar, purgação e cognições de perturbação alimentar melhoram com a gravidez, apesar de tenderem a níveis pré-gravídicos no período pós-parto. Factores psicossociais como a ligação mãe-feto, o suporte do companheiro e o estado de saúde mental pós-parto podem estar associados à perturbação alimentar durante a transição da mulher para a maternidade, na medida em que, se a mulher tiver uma forte ligação ao feto, suporte por parte do companheiro e/ou saúde mental, tende a ter comportamentos mais saudáveis no período pós-parto e um melhor ajustamento na transição para a maternidade (Lai et al, 2006). Astrachan-Fletcher, Veldhuis, Lively, Fowler e Marcks (2008) referem que as exigências da maternidade e as preocupações com a imagem corporal intensificadas pelas alterações corporais da gravidez podem predispor as mulheres a uma exacerbação dos sintomas de perturbações do comportamento alimentar, bem como o desenvolvimento de perturbações do humor no período pós-parto.…”
Section: Perturbações Do Comportamento Alimentar E Gravidezunclassified
See 2 more Smart Citations